Treatment of Gender in The Knight’s Tale, Pararaton, and Arok of Java - Eta Farmacelia Nurulhady (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2022)
This article compares the representations of gender dynamics in a medieval English tale, Geoffrey Chaucer’s The Knight’s Tale, an Indonesian translation of Paraton, a medieval Javanese text, and its twenty-first century Indonesian adaptation, Pramoedya Ananta Toer’s Arok Dedes, which is translated in English as Arok of Java: A Novel of Early Indonesia. The feminist reading of the three texts aims to analyze the treatment of gender in patriarchal society in medieval and modern eras, both in Western and Eastern culture, to show the social constancy and variety of patriarchy that positions women as the Other. The two medieval literary works share similar assigned gender roles that position women in a more passive and submissive stand amidst political upheaval and power struggles. Arok of Java challenges such representation and gives more agency to the female characters. However, those three literary works show how patriarchy lingers across space and time that makes female agency and women’s power almost possible, albeit hard to maintain.